Design and Development of a Self-nanoemulsifying Drug Delivery System for Co-delivery of Curcumin and Naringin for Improved Wound Healing Activity in an Animal Model - Hayat, Ajmal; Shah, Ismail; Jabbar, Abdul; Ullah, Shafi; Shah, Muhammad Raza; Shafique, Muhammad; Balouch, Aziz; Gul, Farah (Planta Medica, 2024)
The present study endeavored to design and develop a self-nanoemulsifying drug delivery system to improve the solubility and dermatological absorption of curcumin and naringin. Curcumin and naringin-loaded self-nanoemulsifying drug delivery system formulations were developed using aqueous phase titration. Phase diagrams were used to pinpoint the self-nanoemulsifying drug delivery system zones. Tween 80 and Labrasol (surfactants), Transcutol (cosurfactant), and cinnamon oil were chosen from a large pool of surfactants, cosurfactants, and oils based on their solubility and greatest nano-emulsion region. Fourier transform infrared spectroscopy, zeta sizer, and atomic force microscopy were used to characterize the optimized formulations and test for dilution and thermodynamic stability. The optimized curcumin-naringin-self-nanoemulsifying drug delivery system demonstrated the following characteristics: polydispersity index (0.412 ± 0.03), % transmittance (97%), particle size (212.5 ± 05 nm), zeta potential (− 25.7 ± 1.80 mV) and having a smooth and spherical droplet shape, as shown by atomic force microscopy. The ability of their combined formulation to cure wounds was tested in comparison to pure curcumin suspension, empty self-nanoemulsifying drug delivery system, and standard fusidic acid. Upon topical administration, the optimized curcumin-naringin-self-nanoemulsifying drug delivery system demonstrated significant wound healing activity in comparison with a pure curcumin suspension, empty self-nanoemulsifying drug delivery system, and standard fusidic acid. Based upon this result, we assume that skin penetration was increased by using the optimized curcumin-naringin-self-nanoemulsifying drug delivery system with enhanced solubility.
Keywords: SNEDDS; curcumin; Curcuma longa; Zingiberaceae; naringin; Citrus reticulata; Rutaceae; wound healing; phase diagrams; thermodynamic stability; topical administration